2015
DOI: 10.1016/j.jmbbm.2015.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucose on the biomechanical function of arterial elastin

Abstract: Elastin is essential to provide elastic support for blood vessels. As a remarkably long-lived protein, elastin can suffer from cumulative effects of exposure to biochemical damages, which can greatly compromise its biomechanical properties. Non-enzymatic glycation is one of the main mechanisms of aging and its effect is magnified in diabetic patients. The purpose of this study is to investigate the effects of glucose on mechanical properties of isolated porcine aortic elastin. Elastin samples were incubated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 49 publications
2
23
0
1
Order By: Relevance
“…These observations suggest that glucose also reduces the piezoelectric response of elastin substantially, which could be related to crosslinking that stiffens elastic fibers and reduces their piezoelectricity. Indeed, we also found increase of tangent modulus in glucose treated elastin (Wang et al 2015; Zou and Zhang 2012). The structural and functional alterations of elastin with glucose exposure may have important physiological implications.…”
Section: Bio-chemo-electro-mechanical Behavior Revealed By Piezosupporting
confidence: 70%
See 2 more Smart Citations
“…These observations suggest that glucose also reduces the piezoelectric response of elastin substantially, which could be related to crosslinking that stiffens elastic fibers and reduces their piezoelectricity. Indeed, we also found increase of tangent modulus in glucose treated elastin (Wang et al 2015; Zou and Zhang 2012). The structural and functional alterations of elastin with glucose exposure may have important physiological implications.…”
Section: Bio-chemo-electro-mechanical Behavior Revealed By Piezosupporting
confidence: 70%
“…In vitro studies have shown that glucose treatments stiffens arterial elastin (Winlove et al 1996), increases the storage and loss modulus (Lillie and Gosline 1996), and also changes the viscoelastic stress relaxation behavior of elastin (Zou and Zhang 2011). Elastin was found to become markedly stiffer and more viscoelastic with excessive glucose exposure (Wang et al 2015; Zou and Zhang 2012). Mechanical testing results (Figure 4) show that the stiffness of elastin increases gradually with glucose treatment.…”
Section: Contribution Of Elastin To Vascular Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experiments showed that under uniaxial strain the surrounding waters of hydration of elastin upon extension undergo more rapid tumbling, pointing to an increase in the entropy of water; this finding indicated that the entropic recoil of hydrated elastin does not arise from a change in water entropy 32 . In a separate study, we investigated the effects of glucose on the elastic recoil of elastin through a combined experimental and computational approach 24,64 . In glucose, elastin is found to exhibit stiffer characteristics as well as viscoelastic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Cytoskeletal mechanics figure courtesy P. Alford; cytoskeletal model figure courtesy W. Ronan; tissue model figure courtesy G. Holzapfel. For further reference, see 9, 19, 21, 49, 72, 160162 .…”
Section: Figurementioning
confidence: 99%